Enhancing the Seismic Performance of Precast RC Frames with Cladding Panels through Setting U-Shaped Dampers and Rocking Walls. (16th June 2020) - Jiang, Qing; Wang, Hanqin; Feng, Yulong; Chong, Xun; Huang, Junqi; Liu, Yibo
Abstract : An approach combining U-shaped dampers (USDs) and rocking walls is proposed in this paper to improve the seismic performance of traditional precast reinforced concrete (RC) frames with cladding panels (PRCFCPs): (1) the steel bar and USD connection methods are adopted at the top and bottom of the cladding panels to use the relative deformation between the cladding panels and the main structure and then dissipate the seismic energy and (2) rocking walls are added to the structure to control the structural deformation profiles. The USD numerical model is calibrated using the test data, and a series of nonlinear pushover analyses, dynamic time-history analyses, and incremental dynamic analyses are successively performed to compare the seismic performance and collapse capacity of the PRCFCP, PRCFCP with USDs (PRCFCP-USD), and PRCFCP with USDs and rocking walls (PRCFCP-USD-RW).The results show that the USDs in the PRCFCP-USD-RW undergo more uniform deformation along the structural height and higher energy dissipation efficiency and the PRCFCP-USD-RW exhibits enhanced seismic performance and collapse capacity, which verify the superiority of the proposed combined approach.